2006
DOI: 10.1128/aac.50.1.126-133.2006
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole as Salvage Therapy for Zygomycosis

Abstract: Zygomycosis, an infection that is associated with significant morbidity and mortality, is becoming common in immunocompromised patients. Posaconazole is a new extended-spectrum azole antifungal that has demonstrated in vitro and in vivo activity against zygomycetes. This report provides the results from the first 24 patients with active zygomycosis who were enrolled in two open-label, nonrandomized, multicentered compassionate trials that evaluated oral posaconazole as salvage therapy for invasive fungal infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
310
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(334 citation statements)
references
References 45 publications
10
310
1
13
Order By: Relevance
“…In a study of 24 subjects for whom posaconazole was used as salvage therapy, the duration varied from 8 to 1,004 d, with a median duration of 182 d. Posaconazole at 200 mg 4 times per day or 400 mg twice per day has shown favorable response rates of 60% and 79%, respectively. 8 In a retrospective series of invasive mucormycosis, posaconazole therapy was successful in 60% of subjects with diabetes mellitus, and its overall success rate was 65% in those with pulmonary mucormycosis. 9 Despite motivation and pursuance, our patient could not continue posaconazole beyond 4 weeks because of cost.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 24 subjects for whom posaconazole was used as salvage therapy, the duration varied from 8 to 1,004 d, with a median duration of 182 d. Posaconazole at 200 mg 4 times per day or 400 mg twice per day has shown favorable response rates of 60% and 79%, respectively. 8 In a retrospective series of invasive mucormycosis, posaconazole therapy was successful in 60% of subjects with diabetes mellitus, and its overall success rate was 65% in those with pulmonary mucormycosis. 9 Despite motivation and pursuance, our patient could not continue posaconazole beyond 4 weeks because of cost.…”
Section: Discussionmentioning
confidence: 99%
“…Two case series and more than 20 case reports of successful treatment with Posaconazole have been published and all conclude a significantly good and complete response. 17,18 It is also cost effective compared with Amphotericin B. A maximum dose of 3 g of lyophilized Amphotericin B in a month long treatment will cost the patient approximately 200,000-300,000 INR (3000 USD approx.)…”
Section: Discussionmentioning
confidence: 99%
“…Further, 6 of the 7 patients experienced complete resolution of infection [131]. Another report including data from 24 patients with active zygomycosis who were enrolled in two open-label, nonrandomized, multicentered compassionate trials that evaluated oral posaconazole as salvage therapy for invasive fungal infections showed that 2 children ages 7 and 17 years of age had partial response to posaconazole and 1 child age 18 had a complete response [132]. To our knowledge, there are no reports on the use of posaconazole in neonates, and we would only consider its use as salvage therapy.…”
Section: Pediatric Clinical Studiesmentioning
confidence: 99%